Tepung Kedelai dan Tepung Daun Kelor dalam Pembuatan Crispy Cookies Sebagai Makanan Selingan Cegah Wasting - Ninis Lestiarini; Rindiani Rindiani (Jurnal Kesehatan, 2023)
Wasting is an acute malnutrition condition that often occurs in toddlers. Wasting can be caused by a lack of nutrition and infectious diseases that can cause metabolic syndrome resulting in drastic weight loss. One way to solve the Wasting problem is by providing high-protein foods. This study aims to identify the characteristics of crispy cookies with the addition of soy flour and moringa leaf flour as a snack to prevent Wasting. The study design used was a Completely Randomized Design (CRD) with 6 formulations of soybean flour: moringa leaf flour, i.e  9: 1, 8: 2, 7: 3, 6: 4, 5: 5, and 4: 6, and repeated 4 times. The results showed that the higher the amount of soy flour, the higher the protein content in crispy cookies. The higher the addition of moringa leaf flour, the more crispy the cookie texture. There is a significant difference (sig < 0.05) between protein content and crispness. The best treatment in this study was the P3 treatment (soy flour: moringa leaf flour = 7: 3) with organoleptic quality characteristics of strong brown color (27.5), slightly strong unpleasant aroma (40.0), crunchy texture (15.8), strong sweet taste (45.0), slightly weak bitter taste (32.5), slightly strong unpleasant aroma (40.0), the protein content of 10.37 g/100g, and fracture strength of 4.25 N. The results of the organoleptic test were the best treatment for toddlers showed that 80% of the toddlers liked it and 20% dislike it. Six pieces of soy flour cookies and moringa leaf flour can be given to children aged 1-3 years to meet 23% of their daily protein needs. For children ages 4-5, 14 pieces per day can fulfill 10% of the daily protein requirement.